FOUNDATIONS OF HEALTH CARE AND TWO HUNDRED YEARS SINCE THE BIRTH OF FLORENCE NIGHTINGALE (1820-1910) - Pelicic, Damir (HEALTH CARE, 2020)
Nursery has existed throughout history and it dates back to the very beginning of humankind. It was mentioned in church books and other written texts but not as a skill or science, but as an occupation reserved for the members of monastic orders, and also for women, that is, mothers, and nuns. First, nursing was an occupation, then a skill, but at the end of the 20th century, it became a scientific discipline. Florence Nightingale is certainly one of the most significant women in the history of nursing, medicine, and society in general because she is the pioneer of the nursing profession that has continuity up to nowadays. She was born on May 12, 1820, in Florence, Italy and died on August 13, 1910, in London. Florence Nightingale worked as a nurse, organizer, researcher, statistician, reformer, writer and a teacher. She reformed nursery and public health. In 1860, she established the school for nurses within St. Thomas’ Hospital and she took care of every protégé. In spite of all obstacles, which she was faced with, and the unenviable position of women in the 19th century, she made a huge move that changed the context of this profession forever. She had a huge influence on the Swiss philanthropist Henry Dunant (1828-1910), who was the founder of The Red Cross. In 1867, the International Council of Nurses proclaimed that her birthday would be the International Nurses Day. She was the first woman who was awarded the Medal of virtues. In 1908, she was conferred the Order of Merit by King Edward. She wrote more than 200 books and the Pledge. ˮI appreciate my success to this that I have never made or accept any excuse.ˮ Florence Nightingale